(untitled) - Baltzan, Paige (New York, 2013)
Business Driven Technology5e offers you the flexibility to customize your course according to your needs and the needs of your students by covering only essential concepts and topics in the five core units, while providing additional in-depth coverage in the business and technology plug-ins
Keywords: Information resources management,Industrial management,Công nghệ thông tin,Quản lý tài nguyên thông tin; Technological innovations,Đổi mới công nghệ